Characterization of Vapor Capillary Geometry in Laser Beam Welding of Copper with 515 nm and 1030 nm Laser Beam Sources by Means of In Situ Synchrotron X-ray Imaging - Kaufmann, Florian; Forster, Carola; Hummel, Marc; Olowinsky, Alexander; Beckmann, Felix; Moosmann, Julian; Roth, Stephan; Schmidt, Michael (Metals, 2023)
Laser welding of copper is being used with increasing demand for contacting applications in electric components such as batteries, power electronics, and electric drives. With its local, non-contact energy input and high automation capability enabling reproducible weld quality, this joining technology represents a key enabler of future mobility systems. However, a major challenge in process design is the combination of energy efficiency and precise process guidance in terms of weld seam depth and defect prevention (i.e., spatter and melt ejections) due to the high electrical and thermal conductivity of copper. High-power lasers in the near infrared wavelength range (𝜆 ≈ 1 μm) and excellent beam quality provide an established joining solution for this purpose; nevertheless, the low absorptivity (≤5%) advocates novel beam sources at visible wavelengths due to altered absorptivity (40% at 515 nm) characteristics as an improved tool. In order to understand the influence of laser wavelength and process parameters on the vapor capillary geometry, in situ synchrotron investigations on Cu-ETP with 515 nm and 1030 nm laser sources with the same spot diameter are compared. The material phase contrast analysis was successfully used to distinguish keyhole and melt pool phase boundaries during the welding process. A significantly different sensitivity of the keyhole depth in relation to the feed rate was found, which is increased for the infrared laser. This behavior could be attributed to the increased effect of multiple reflections at 1030 nm.<br

High current contacts for integrated electric drives Serienfähige Hochstromkontakte für integrierte elektrische Fahrzeugantriebe - Schriefer, Thomas; Rauh, Hubert; Hofmann, Maximilian; Schreibmüller, Nicolas; Nusser, Tobias; Horwath, Christian; Moritz, Werner; Moosmann, Nico; Deibert, Andreas; Gerberich, Thorsten; Schaumberger, Kerstin; Kaufmann, Florian; et al. (wt Werkstattstechnik - Online, 2019)
The increasing level of mechatronic integration in the electric power-train of automotive vehicles is overcome by innovative power connectors. Utilizing analytical, numerical and experimental procedures, high-current connectors are developed to transmit electrical loads within the key components electric motor, power electronics and battery system.
CRIS-Team Scopus Importer:2022-06-05

Improving process reliability by means of detection of weld seam irregularities in copper via thermographic process monitoring - Schaumberger, Kerstin; Beck, M.; Saffer, Judith; Kaufmann, Florian; Ermer, J.; Roth, S.; Schmidt, Michael (Procedia Manufacturing, 2019)
Laser beam welding plays an important role in automotive industry as it offers a number of advantages. These include contactless joining, localized energy input, thermally and mechanically durable welds and low electrical contact resistance of the bonded connections. The latter is exploited in the laser beam welding of copper contacts as used for electrical connections in e-mobility. However, copper entails a higher susceptibility to seam defects due to the metallurgical properties compared to, for example, car body materials which in many cases are processed by laser beam as well. In order to meet the high standards of the automotive industry an inline validation of the connections is essential. A suitable method is the monitoring of the welding process by means of thermography which has already proven itself for other metals and joining techniques but has not yet been investigated in detail for laser beam welding of copper. Consequently, this paper deals with the possibilities of thermographic process monitoring in laser beam welding of copper components. It examines the extent to which defects can be registered; so far pores have been detected reliably up to a minimal diameter of 0.5 mm.
CRIS-Team Scopus Importer:2019-10-01
Keywords: Copper; Defects; Infrared thermography; Inline monitoring; Laser beam welding

Influence of Laser Beam Intensity Distribution on Keyhole Geometry and Process Stability Using Green Laser Radiation - Kaufmann, Florian; Maier, Andreas; Schrauder, Julian; Roth, Stephan; Schmidt, Michael (Lecture Notes in Mechanical Engineering, 2024)
Laser beam welding is being more frequently employed to join copper materials. The use of green laser radiation shows the advantage of significantly higher absorptivity for these metals compared to near-infrared radiation. Therefore, a change in process stability and defect formation is expected. In addition, the effect of modifying the intensity distribution on the formation of weld seam defects and the geometric properties of the seam in deep penetration mode is largely unexplored. Thus, the aim of this work is the characterization of process dynamics and defect formation in correlation to the focal position and the intensity distribution by means of high-speed imaging and metallographic analysis. A significant reduction of seam imperfections is observed for a gaussian beam profile compared to a Top Hat intensity distribution. An advantageous seam shape and the earlier onset of the deep penetration welding process are favorable reasons for the application of this intensity distribution, while medium to high processing speeds further improve the processing quality.
CRIS-Team Scopus Importer:2023-09-29
Keywords: electromobility; green laser radiation; intensity distribution; Laser beam welding; process observation; quality improvement

Influence of plume attenuation under high power laser welding of copper using visible wavelengths - Ermer, Jakob; Maier, Andreas; Schmidt, Michael; Kaufmann, Florian; Roth, Stephan (Journal of Laser Applications, 2021)
Joining of copper materials has become a key factor in laser material processing of electric components like electric engines, batteries, or power electronics. A paramount challenge is the design of the laser welding process, which has to fulfil the requirements of high energy efficiency and highest seam quality at the same time. By now, high-power laser beam sources emitting visible laser radiation are available to promote the well-suited noncontact joining method, which is furthermore characterized by local energy input and high automation potential. These laser sources can now face the challenges of welding highly conductive and reflective materials, such as copper, which originate mainly in the low absorption of conventionally used infrared wavelengths at room temperature and the rapid jump of absorptivity at transition from solid to liquid state. An increase in absorption of electromagnetic radiation to more than 40% for copper at room temperature for λ = 515 nm leads to increasing energy input in the material and promotes a more efficient process therefore. However, up to now, mostly the heat conduction welding regime has been examined and the effects of shorter wavelengths on deep penetration welding have not been understood in detail. A strong deviation in weld seam depth between infrared and green laser radiation is observed for identical process parameters depending on the use of additional gas supply [F. Kaufmann, A. Meier, J. Ermer, S. Roth, and M. Schmidt, “Influence of defocusing in deep penetration welding of copper by using visible wavelength,” in Proceedings of the Eleventh International WLT-Conference on Lasers in Manufacturing, Munich, 21-24 June 2021 (M. Reth, Munich, 2021)]. Consequently, radiation attenuation by the metal vapor inside and above the keyhole plays a substantial role in the case of 515 nm laser welding [M. Haubold, A. Ganser, T. Eder, and M. F. Zäh, “Laser welding of copper using a high power disc laser at green wavelength,” Procedia CIRP 74, 446-449 (2018)]. In this work, we investigate in situ measurements of plume attenuation during laser beam welding of copper with 515 and 1030 nm laser beam sources. Both laser sources are equipped with comparable optical setups to achieve identical focal diameters on the material surface. We investigate the plume characteristics in the deep penetration welding mode of copper. A range of industry-relevant process parameters are investigated to create a basis for comparison with theoretical models. It is found that a significant difference in the attenuation of both laser wavelengths occurs in the case of deep penetration welding copper specimen and blowing the vapor plume out of the beam path is recommended therefore for an efficient welding process.
CRIS-Team Scopus Importer:2021-10-01

Influence of process parameters on microstructural and mechanical properties of duplex stainless steel 2205 (1.4462) processed by DED-LB{M - Maier, Andreas; Munk, Alexander; Kühl, Andrea; Rühr, Manuel; Hentschel, Oliver; Kaufmann, Florian; Schrauder, Julian; Roth, Stephan; Schmidt, Michael (Procedia CIRP, 2022)
Duplex stainless steels (DSS) combine excellent corrosion resistance with outstanding mechanical properties. Typical applications can be found in chemical, gas and offshore industries, where corresponding components usually feature a high degree of customization. This makes additive manufacturing an economically interesting production approach. However, a major challenge in additive manufacturing of DSS is a precise process control to achieve the required material properties. In this work, DED-LBwas used to process DSS 2205. A multistage experimental procedure was developed to generate nearly fully dense cuboidal specimens (relative density > 99.9 %). In addition, the complex interaction mechanisms between process parameters and resulting material properties such as microstructure and hardness were investigated. For specific process conditions, the desired ferrite-austenite balance of DSS could be obtained. Furthermore, the hardness was found to decrease with increasing build height and correlates with gran size as well as the slightly decreasing ferrite content.<br

Investigation of coupling efficiency in laser beam welding of copper materials using brilliant infrared and green laser radiation - Kaufmann, Florian; Möttingdörfer, Robert; Roth, Stephan; Schmidt, Michael (Journal of Manufacturing Processes, 2024)
One of the fundamental effects of laser material processing is laser beam absorption. The absorptivity in the laser welding process is subjected to temporal and spatial fluctuations due to temperature and phase changes and is furthermore dependent on the wavelength used. Currently, experimental absorptivity data for copper at high temperatures is rarely available, and discussions of investigation are largely based on theoretical assumptions. However, this property is essential for a fundamental understanding of the phenomena involved in laser-matter interaction and for efficient process design, especially for the emerging manufacturing processes for electric vehicles, where copper materials are widely used. In this work, a specially designed, low-cost experimental arrangement was built to measure the laser absorption during the process in different welding modes, which enables the derivation of coupling efficiency values in these regimes. Brilliant laser beam sources with λ = 515 nm and λ = 1030 nm radiation and comparable spot characteristics on the workpiece were used for the investigation. Results captured with microsecond resolution show several important features, including the points of melting and vapor capillary formation for both pulsed and continuous process guiding. General tendencies known from literature could be confirmed by our measurements, and the comparison of the absorptivity data with microscopic inspection and a weld seam cross-sectional analysis shows a significant correlation of the characteristics.
CRIS-Team Scopus Importer:2024-10-25
Keywords: Absorptivity; Copper; Energy coupling; EV manufacturing; Green laser radiation; Laser beam welding

Laser-based droplet brazing – Influence of additionally induced thermal energy on joint quality - Schrauder, Julian; Ermer, Jakob; Maier, Andreas; Frick, Thomas; Kaufmann, Florian; Müller, Markus; Schmidt, Michael; Roth, Stephan (Procedia CIRP, 2022)
The demand for semiconductors and microelectronic components is greater than ever and will continuously rise in the future due to increasing automation and digitalization. Also, there is a growing need for robust, high-temperature resistant electrical connections which are essential for the circuit function. Previous investigations have shown that laser-based droplet brazing can create high temperature stable joints e.g. on thin silver layers, without applying an external force on the micro-component to be joined. In order to expand the application field of this process, further combinations of different brazing and substrate materials are investigated. In this paper the influence of additionally induced thermal energy at the diffusion zone was analyzed via shear tests. The studies show, that using brazing alloy CuSn11 in combination with a substrate heating provides the most robust joints on the tested substrate material.<br

Laser beam welding of heat-resistant mixed joints using laser-based pre- and post-heating - Saffer, Judith; Dörres, T; Schaumberger, Kerstin; Ermer, Jakob; Kaufmann, Florian; Wittmann, Alexander; Roth, Stephan; Schmidt, Michael (Procedia CIRP, 2020)

Laser beam welding of Ti-6Al-4V hybrid-parts from additively manufactured elements and sheet metal - Huber, Florian; Mann, Vincent; Kaufmann, Florian; Schmidt, Michael (Lasers in Manufacturing (LiM) 2019, 2019)

Qualification of a system technology for selective laser-based quasi-simultaneous soldering with an integrated pyrometric process control - Ermer, Jakob; Saffer, Judith; Schaumberger, Kerstin; Kaufmann, Florian; Wittmann, Alexander; Roth, Stephan; Schmidt, Michael (Procedia CIRP, 2020)
Due to the tendency of miniaturization of electronic components, the increased use of thermally sensitive circuit boards e.g. LCDs, a large number of requirements arises for a selective laser beam soldering process. To enhance the possibilities of selective soldering, a system technology for quasi-simultaneous, pyrometric controlled laser soldering was qualified. The systems capability is to enable a controlled laser soldering process at different spot-sizes, varying electronic device layouts and different irradiation strategies. An inline emission measurement via pyrometer gains live-data from the soldering process, evaluates them and transfers them in a closed loop cycle to the laser power control. To enable a process control over a large scanning field, a chromatic corrected f-theta optic, which compensates the chromatic aberration between laser and pyrometer wavelength was used. Different scanning strategies and varying laser power profiles have been evaluated regarding their influence on the process quality.<br
Keywords: selective laser soldering; pyrometric process control; microelectronic devices; chromatic corrected f-theta lens; fiber laser

Tailored laser beam shapes for welding of copper using green laser radiation - Kaufmann, Florian; Roth, Stephan; Schmidt, Michael (International Journal of Advanced Manufacturing Technology, 2024)
The rapid development of laser beam sources and adapted welding technologies in recent years lead to an increased use of laser welding techniques in automated production nowadays. Especially its precision and local energy input are key features for joining applications in electric vehicle components, where joints have to meet both mechanical and electrical requirements as current-carrying connections. However, the copper materials used are difficult to weld due to their physical properties, making a stable process with fewest seam imperfections only feasible within a limited process window. Recently available beam sources emitting visible laser radiation have proven to overcome the low absorptivity at process start, but spattering is still a prone defect significantly affecting process efficiency and quality. Literature approaches for modifying the energy input point to laser beam shaping as a method for reducing process imperfections, which, however, has not been extensively researched in copper processing using green laser radiation. Thus, this study investigates the influence of a shaped intensity profile for visible laser radiation created with a reflective diffractive optical element in laser beam welding with laser powers up to 3 kW. A characterization of the process dynamics is performed by use of high-speed imaging, and metallographic analysis is used to elaborate benefits of the applied beam shapes. With beam shaping, an enlarged heat conduction welding regime and an advantageous seam shape are found. Furthermore, a decrease in spatter formation during deep penetration welding is detected for the elliptical beam profile, which correlates with an oscillation movement of the capillary.
CRIS-Team Scopus Importer:2024-02-16
Keywords: Beam shaping; Copper; Diffractive optical element; Green laser radiation; Laser beam welding; Process observation

Towards an Understanding of the Challenges in Laser Beam Welding of Copper – Observation of the Laser-Matter Interaction Zone in Laser Beam Welding of Copper and Steel Using in Situ Synchrotron X-Ray Imaging - Kaufmann, Florian; Schrauder, Julian; Hummel, Marc; Spurk, Christoph; Olowinsky, Alexander; Beckmann, Felix; Moosmann, Julian; Roth, Stephan; Schmidt, Michael (Lasers in Manufacturing and Materials Processing, 2023)
The increasing demand for contacting applications in electric components such as batteries, power electronics and electric drives is boosting the use of laser-based copper processing. Laser beam welding is a key for an efficient and high-quality electric vehicle production due to its local, non-contact energy input and high automation capability enabling reproducible weld quality. Nevertheless, a major challenge in process design is the combination of energy-efficiency and precise process guidance with regard to weld seam depth and defect prevention (i.e. spatter, melt ejections), partly caused by the high thermal conductivity of copper. High power lasers in the near infrared range and emerging visible laser beam sources with excellent beam quality can provide a suitable joining solution for this purpose. However, the underlying physical phenomena are currently only partly understood and a reflection on the challenges of laser beam welding of copper compared to well researched steel processing has not yet been carried out. In order to improve the understanding of the effect of the different material properties and the influence of process parameters on the vapor capillary and melt pool geometry in laser beam welding, in situ synchrotron investigations on Cu-ETP and S235 using 515 and 1030 nm laser sources were conducted. The material phase contrast analysis was successfully used to distinguish vapor capillary and melt pool phase boundaries during the welding process with high spatial and temporal resolution up to 5 kHz. A significantly different vapor capillary geometry and sensitivity to parameter variation were found between the steel and copper material. In addition, the visualization of characteristic melt flows revealed different melt pool dynamics and a pronounced eddy close to the melt pool surface for copper, which is assumed to be causal for the observation of pronounced spatter formation during copper welding in a certain process window.
CRIS-Team Scopus Importer:2023-09-22
Keywords: Copper; Electromobility; Keyhole welding; Process observation; X-ray phase contrast observation

Why Color Matters—Proposing a Quantitative Stability Criterion for Laser Beam Processing of Metals Based on Their Fundamental Optical Properties - Kohl, Stefanie; Kaufmann, Florian; Schmidt, Michael (Metals, 2022)
With its excellent automation capability and localized energy input enabling precise, reproducible welds, laser beam welding represents a preferred industrial joining technology. Electro-mobility drastically increases the need for defect-free and automatable copper joining technologies. However, copper welds that are produced with state-of-the-art infrared lasers often suffer from spattering and porosity. Recent publications show distinct improvements using novel beam sources at visible wavelengths, attributing them to increased absorptivity. Nevertheless, this cannot fully explain the steadier process behavior. This wavelength-dependent process stability has not yet been investigated sufficiently. Therefore, we have developed a predictive material-dependent criterion indicating process stability based on the example of copper heat-conduction spot welding. For this purpose, we combined energy balances with thermo-physical material properties, taking into account the wavelength and temperature dependence of the optical properties. This paper presents the key mechanism that we identified as decisive for process stability. The criterion revealed that X-points (unique, material-specific wavelengths) represent critical stability indicators. Our calculations agree very well with experimental results on copper, steel and aluminum using two different wavelengths and demonstrate the decisive, material-dependent wavelength impact on process stability. This knowledge will help guide manufacturers and users to choose and develop beam sources that are tailored to the material being processed.<br
Keywords: laser beam welding; copper welding; wavelength dependence; optical properties; analytical modeling